RESTORATIVE JUSTICE IN CRIMINAL DEFAMATION ON SOCIAL MEDIA: A LEGAL PERSPECTIVE AND IMPLEMENTATION IN INDONESIA - Widodo (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
This research discusses restorative justice in the crime of defamation on social media, focusing on the legal perspective and its implementation in Indonesia. Defamation through social media has become an increasingly relevant issue in today's digital era. The restorative justice approach offers an alternative in resolving defamation cases that can restore the relationship between the perpetrator and the victim.The purpose of this research is to find out how is the implementation of restorative justice in the settlement of criminal defamation in social media? This research uses a normative juridical approach, with a literature study that includes various sources such as scientific writings or articles in the form of books, online media, dissertations or other literature. The results showed that the implementation of restorative justice in the settlement of criminal defamation in Indonesia is still limited and faces various obstacles. These obstacles include a lack of awareness and understanding of the concept of restorative justice, lack of support from relevant institutions, and challenges in identifying and involving all parties involved. Restorative Justice has great potential as an effective approach in resolving defamation cases. This approach focuses on recovery and reconciliation between the perpetrator, the victim, and the community.